Ouabain – a double-edged sword in tumor development and progression? a review of half a century - Weidemann, Heidrun; Sarsour, Alaa Daoud; Brodie, Chaya (Frontiers in Physiology, 2025)
Since their first discovery as potential anti-cancer drugs there is increasing evidence that cardiotonic steroids e.g., Ouabain have anti-tumor properties by interacting with their natural receptor the Na+-K+-ATPase (NKA) and by inducing diverse intracellular signaling pathways. It is well established that the NKA represents a signal transducer that is partly independent from its pump activity. In the early 90ies endogenous Ouabain (EO) was discovered in the serum of different species, including human beings. It was demonstrated that Ouabain is synthesized and released from the adrenal gland. The concept of endogenous Ouabain as a “stress hormone” playing important roles in the regulation of hypertension, volume homeostasis, cardiac function and, last but not least, cancer was established. We developed the hypothesis that long-lasting stress with adrenal exhaustion i.e., very low endogenous Ouabain levels may predispose to tumorigenesis. On the contrary, some authors recently have questioned the tumor-protective role of Ouabain and claimed that endogenous Ouabain promotes tumor escape mechanisms. In order to clarify these and other opposing or contradictious data we will summarize in this review PubMed data from the last 50 years about “Ouabain and cancer”. We will demonstrate that overwhelming evidence speaks in favor of an anti-tumor effect of Ouabain. Exogenous Ouabain has been shown to be identical to endogenous Ouabain, hence we conclude that a potential harmful role of endogenous Ouabain is minor compared to the huge potential benefit of Ouabain in defeating and suppressing the development of cancer.